(untitled) (Ágora UNLaR, 2019)
La apelación a una identidad negra nacional e histórica en los escritos de varios intelectuales afroestadounidenses del Siglo XIX constituye una intervención a la ciencia racial predominante de la época, en cuanto revierte, deconstruye y refuta los argumentos esclavistas desde un contradiscurso. Asimismo, conforma un acto político en cuanto pretende reconstruir una comunidad africana imaginada, con un pasado ilustre, y un imaginario especulativo con la esperanza de un futuro afro-estadounidense tras la eventual emancipación. El siguiente trabajo indaga sobre las fuentes que ilustran este contradiscurso y las pone en diálogo con el discurso de la ciencia racial y, en especial, la historia natural, en un contexto donde lo científico era un concepto fluido y abarcativo, muchas veces apoyado en fuentes bíblicas. THE BLACK NATIONAL AND HISTORICAL IDENTITY IN AFRICAN AMERICANS‘ ENGAGEMENTS IN 19th CENTURY SCIENCE Abstract The promotion of a black national and historical identity in 19th-Century African American intellectuals ‘writings accounts for a series of scientific engagements and responses to the mainstream racial science of the time. These scientific engagements by black intellectuals reverse, deconstruct and refute pro-slavery arguments through a counterdiscourse. Furthermore, they constitute a political act, as they aim at the reconstruction of an imagined African community with an illustrious past, and a speculative imaginary which builds hope for the future of African Americans in the wake of potential emancipation. This paper inquires into several sources that illustrate this counterdiscourse against racial science, and Natural History in particular, in a context in which the very concept of science was a capacious and fluid one, many times founded on biblical sources. Key Words: 19th century science; african american studies; scientific engagements by black intellectuals; black national and historical identity